Ribociclib plus letrozole versus letrozole alone in patients with de novo HR+, HER2- advanced breast cancer in the randomized MONALEESA-2 trial - O'Shaughnessy, Joyce; Petrakova, Katarina; Sonke, Gabe S; Conte, Pierfranco; Arteaga, Carlos L; Cameron, David A; Hart, Lowell L; Villanueva, Cristian; Jakobsen, Erik; Beck, Joseph T; Lindquist, Deborah; Souami, Farida; et al. (Breast cancer research and treatment, 2018)
PURPOSE: Determine the efficacy and safety of first-line ribociclib plus letrozole in patients with de novo advanced breast cancer. METHODS: Postmenopausal women with HR+ , HER2- advanced breast cancer and no prior systemic therapy for advanced disease were enrolled in the Phase III MONALEESA-2 trial (NCT01958021). Patients were randomized to ribociclib (600 mg/day; 3 weeks-on/1 week-off) plus letrozole (2.5 mg/day; continuous) or placebo plus letrozole until disease progression, unacceptable toxicity, death, or treatment discontinuation. The primary endpoint was investigator-assessed progression-free survival; predefined subgroup analysis evaluated progression-free survival in patients with de novo advanced breast cancer. Secondary endpoints included safety and overall response rate. RESULTS: Six hundred and sixty-eight patients were enrolled, of whom 227 patients (34%; ribociclib plus letrozole vs placebo plus letrozole arm: n = 114 vs. n = 113) presented with de novo advanced breast cancer. Median progression-free survival was not reached in the ribociclib plus letrozole arm versus 16.4 months in the placebo plus letrozole arm in patients with de novo advanced breast cancer (hazard ratio 0.45, 95% confidence interval 0.27-0.75). The most common Grade 3/4 adverse events were neutropenia and leukopenia; incidence rates were similar to those observed in the full MONALEESA-2 population. Ribociclib dose interruptions and reductions in patients with de novo disease occurred at similar frequencies to the overall study population. CONCLUSIONS: Ribociclib plus letrozole improved progression-free survival vs placebo plus letrozole and was well tolerated in postmenopausal women with HR+, HER2- de novo advanced breast cancer.
Keywords: Receptors, Estrogen; dospělí; Kaplan-Meier Estimate; nádory prsu; Female; kritéria léčebné odpovědi; Adult; ženské pohlaví; Kaplanův-Meierův odhad; Aminopyridines; postmenopauza; doba přežití bez progrese choroby; puriny; Time Factors; časové faktory; lidé; Breast; leukopenie; prsy; Breast Neoplasms; receptory progesteronu; Receptors, Progesterone; receptory pro estrogeny; Aged, 80 and over; Antineoplastic Combined Chemotherapy Protocols; Leukopenia; protokoly protinádorové kombinované chemoterapie; Response Evaluation Criteria in Solid Tumors; Middle Aged; Incidence; incidence; Aged; Letrozole; Purines; Chemotherapy-Induced Febrile Neutropenia; lidé středního věku; senioři nad 80 let; senioři; febrilní neutropenie vyvolaná chemoterapií; Postmenopause; Progression-Free Survival; letrozol; aminopyridiny; Humans